High-Protein Complementary Food Powder Based on Fermented Cow’s Milk with Composite Flour - Yosi Irene Putri; Helmizar Helmizar; Utami Ariyasra; Nurul Azizah (GLOBAL HEALTH SCIENCE GROUP, 2026)
Adequate nutrition for infants during crucial periods is crucial for their development and growth. Providing nutrient-dense complementary foods (CF) and probiotics is crucial for infants, not only for high protein intake but also for the addition of probiotics in CF to maintain digestive tract health and improve nutrient absorption. This study aims to evaluate the nutritional and organoleptic characteristics of the development of a high-protein and probiotic CF formula with composite flour (corn, red bean, and soybean) and cow's milk curd flour. The best treatment will be tested for amino acid profiles. The method is experimental with a Completely Randomized Design (CRD) consisting of 4 treatments and 4 replications. Data were collected laboratory proximate analysis using Soxhlet, and Kjeldahl, organoleptic data using hedonic tests with panelists through structured questionnaires, and amino acid profiles were analyzed using High Performance Liquid Chromatography (HPLC). The water content ranged from 8.29% - 8.75%, the ash content ranged from 3.65% - 3.90%, the fat content ranged from 17.08% - 20.24%, the protein content ranged from 17.77% - 19.21%, and the carbohydrate content ranged from 48.12% - 52.87%. The organoleptic test results for formulas F3 and F4 were most acceptable to the panelists based on the results of sensory parameters. The highest essential amino acid profiles were methionine and isoleucine while the non-essential amino acids were glutamic acid and aspartic acid. The addition of cow's milk curd flour can increase protein and fat while the addition of composite flour increases carbohydrates.